Studi Kasus: Penanganan Prolapsus Ani dengan Enterektomi pada Kucing Domestik di Rumah Sakit Hewan Jawa Barat - Rasdiyanah, Rasdiyanah; Mustain, Fathir Alparabi; Ris, Adryani; Suriansyah, Suriansyah; Citra Septaningsih, Andi; Feribertus Rinca, Korbinianus (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Domestic cats are one of the types of animals commonly kept as petsin Indonesia. Stray cats are a type of domestic cat that can also bekept as pets because they are capable of socializing with humans.However, due to their behavioral patterns and the lack of proper petmanagement, stray cats are often exposed to diseases and can becomecarriers for other cats. On September 9, 2024, a male cat named Kucil,approximately 4 months old and weighing around 2 kg, was broughtto the West Java Provincial Animal Hospital with a complaint of amass protruding from the anus. The purpose of this case study is todetermine the diagnosis and management of prolapsed rectum indomestic cats. The diagnostic methods used included anamnesis,physical examination, and supporting tests, such as blood hematology.The physical examination revealed a body temperature of 38.5°C anda capillary refill time (CRT) of less than 2 seconds. Upon performingan inspection of the anus, a mass was found protruding through theanus, leading to the diagnosis of prolapsed rectum in Kucil. Thetreatment involved an enterectomy or surgical removal of the intestinethat had prolapsed from the anus. Post-operative therapy includedantibiotics, anti-inflammatory drugs, and vitamins